PERAN PONDOK PESANTREN DALAM MEMBANGUN KEMANDIRIAN EKONOMI BERBASIS PEMBERDAYAAN MASYARAKAT - Fathurrahman Al-Ghifari; Siti Humaira Nasution (Yayasan An-Nur Meunara Baro, 2026)
The dependence of Islamic boarding schools (pesantren) on external assistance often hampers institutional development and missionary autonomy. This study aims to analyze the economic empowerment mechanism at Pondok Pesantren Modern